Codigestão anaeróbia de dejetos de suínos e níveis de inclusão de óleo de descarte - Orrico, Ana C. A.; Sunada, Natália Da S; Lucas, Jorge De [UNESP]; Orrico, Marco A. P; Schwingel, Alice W. [UNESP] (Associação Brasileira de Engenharia Agrícola, 2015)
Swine manure and lipid residue co-digestion has been widely explored with improvements in substrate degradation, digestion and consequently biogas yield. Thus, we evaluated performance of digesters supplied with swine manure and increasing discarded oil levels, by means of potential of biogas production, and reductions of total solid content (TS), volatile solids (VS) and chemical oxygen demand (COD). To develop co-digestion tests, we prepared substrates composed by swine manure, discarded oil (with 0, 2, 4, 6, 8, 10 and 12% oil in TS substrate), water for dilution of residues and inoculum, having a initial concentration at 4% TS to supply batch-digesters. Maximum TS and VS reductions were 36.8 and 41.1% and occurred at 5.2 and 5.8% oil in substrate. Inclusions of 5.4 and 6.1% oil allowed a potential production range of 222.9 and 263.6 liters of biogas per TS and VS kilogram, which were superior in 10.8 and 5.5 to the observed yields for initial dose of 0% oil. Oil included into substrate with swine manure at doses between 5 and 6% have improved biogas yield.

A codigestão dos dejetos de suínos e dos resíduos lipídicos vem sendo amplamente explorada, com melhorias na degradação dos substratos em digestão e, consequentemente, dos rendimentos de biogás. Assim, foram avaliados os desempenhos de biodigestores abastecidos com dejetos de suínos e crescentes níveis de óleo de descarte, por meio das produções e potenciais de produção de biogás, reduções dos teores de sólidos totais (ST), sólidos voláteis (SV) e da demanda química de oxigênio (DQO). Para o desenvolvimento do ensaio de codigestão, foram preparados substratos compostos por dejetos de suínos, óleo de descarte (nas proporções de 0; 2; 4; 6; 8; 10 e 12% de óleo em relação aos teores de ST do substrato), água para diluição destes resíduos e inóculo, contendo teor inicial de 4,0% de ST e abastecimento dos biodigestores batelada. As máximas reduções de ST e SV foram de 36,8 e 41,1% e ocorreram nos níveis de 5,2 e 5,8% de óleo aos substratos. As inclusões de 5,4 e 6,1% de óleo permitiram o alcance de potenciais de 222,9 e 263,6 litros de biogás por kg de ST e SV adicionados, que foram superiores em 10,8 e 5,5% aos rendimentos observados para a dose contendo 0% de óleo. A inclusão de óleo na composição de substratos contendo dejetos de suínos nas doses entre 5 e 6% melhora os rendimentos de biogás.
Anaerobic co-digestion of swine manure and increasing levels of discarded oil
Keywords: digester; swine industry; total solids; volatile solids; biodigestor; suinocultura; sólidos totais; sólidos voláteis